2023
DOI: 10.1111/tpj.16453
|View full text |Cite
|
Sign up to set email alerts
|

The RAV transcription factor TEMPRANILLO1 involved in ethylene‐mediated delay of chrysanthemum flowering

Hua Cheng,
Qingguo Wang,
Zixin Zhang
et al.

Abstract: SUMMARYTEMPRANILLO1 (TEM1) is a transcription factor belonging to related to ABI3 and VP1 family, which is also known as ethylene response DNA‐binding factor 1 and functions as a repressor of flowering in Arabidopsis. Here, a putative homolog of AtTEM1 was isolated and characterized from chrysanthemum, designated as CmTEM1. Exogenous application of ethephon leads to an upregulation in the expression of CmTEM1. Knockdown of CmTEM1 promotes floral initiation, while overexpression of CmTEM1 retards floral transit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 85 publications
(111 reference statements)
1
5
0
Order By: Relevance
“…Transcription factors are proteins that help to turn specific genes “on” or “off” by binding to nearby DNA [ 45 , 46 , 47 , 48 , 49 ]. Accumulating evidence has revealed the various functions of RAV transcription factors in the processes of seed germination [ 17 , 21 , 29 ], seedling growth and development [ 16 , 17 , 18 , 50 ], flowering [ 11 , 19 ], and abiotic and biotic stresses [ 22 , 23 , 24 , 29 , 34 , 51 ]—salt stress in particular [ 26 , 27 , 28 , 30 , 50 ]. Among the multiple abiotic stresses, salt stress is one of the most important factors threating plants during their entire growth processes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Transcription factors are proteins that help to turn specific genes “on” or “off” by binding to nearby DNA [ 45 , 46 , 47 , 48 , 49 ]. Accumulating evidence has revealed the various functions of RAV transcription factors in the processes of seed germination [ 17 , 21 , 29 ], seedling growth and development [ 16 , 17 , 18 , 50 ], flowering [ 11 , 19 ], and abiotic and biotic stresses [ 22 , 23 , 24 , 29 , 34 , 51 ]—salt stress in particular [ 26 , 27 , 28 , 30 , 50 ]. Among the multiple abiotic stresses, salt stress is one of the most important factors threating plants during their entire growth processes.…”
Section: Discussionmentioning
confidence: 99%
“…Transcription factors play vital roles in plant growth and plant responses to abiotic stresses [ 9 , 10 ]. The RAV transcription factors contain a B3 DNA-binding domain and/or an APETALA2 (AP2) DNA-binding domain [ 11 , 12 , 13 ]. RAV transcription factors regulate the transcript expression of downstream target genes by binding to core sequences of 5′-CAACA-3′ and 5′-CACCTG-3′ [ 14 ] and function in regulating vegetative growth [ 15 , 16 , 17 ], flowering [ 11 , 18 , 19 ], phytohormone signal transduction [ 20 , 21 ], biotic stresses response [ 22 , 23 , 24 , 25 ], and abiotic stresses response such as salt [ 21 , 26 , 27 , 28 ], and drought [ 21 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, the RAV family genes ETHYLENE RESPONSE DNA BIND-ING FACTOR1 to 4 (EDF1-EDF4) in Arabidopsis are involved in ethylene-mediated petal abscission [30], and the AtEDF1/2/4 genes, which act downstream of the embryonic leaf identity gene FUSCA3, participate in ethylene-mediated developmental transitions [37]. In addition, recent findings have revealed that the chrysanthemum RAV family transcription factor CmTEM1 takes part in the ethylene-mediated floral repression by targeting the APETALA1/FRUITFULL-like1 (CmAFL1) gene directly [38]. Although all of the above studies revealed that RAV genes are involved in ethylene-mediated growth and developmental processes, whether they are involved in ethylene-mediated stress responses needs to be followed up.…”
Section: Introductionmentioning
confidence: 99%